Transcriptional repression of NFKBIA triggers constitutive IKK‐ and proteasome‐independent p65/RelA activation in senescence. (18th January 2021) - Kolesnichenko, Marina; Mikuda, Nadine; Höpken, Uta E; Kärgel, Eva; Uyar, Bora; Tufan, Ahmet Bugra; Milanovic, Maja; Sun, Wei; Krahn, Inge; Schleich, Kolja; von Hoff, Linda; Hinz, Michael; et al.
Abstract: The IκB kinase (IKK)‐NF‐κB pathway is activated as part of the DNA damage response and controls both inflammation and resistance to apoptosis. How these distinct functions are achieved remained unknown. We demonstrate here that DNA double‐strand breaks elicit two subsequent phases of NF‐κB activation in vivo and in vitro, which are mechanistically and functionally distinct. RNA‐sequencing reveals that the first‐phase controls anti‐apoptotic gene expression, while the second drives expression of senescence‐associated secretory phenotype (SASP) genes. The rapidly activated first phase is driven by the ATM‐PARP1‐TRAF6‐IKK cascade, which triggers proteasomal destruction of inhibitory IκBα, and is terminated through IκBα re‐expression from the NFKBIA gene. The second phase, which is activated days later in senescent cells, is on the other hand independent of IKK and the proteasome. An altered phosphorylation status of NF‐κB family member p65/RelA, in part mediated by GSK3β, results in transcriptional silencing of NFKBIA and IKK‐independent, constitutive activation of NF‐κB in senescence. Collectively, our study reveals a novel physiological mechanism of NF‐κB activation with important implications for genotoxic cancer treatment. SYNOPSIS: DNA damage induces two kinetically and functionally distinct phases of NF‐κB activation. The first is anti‐apoptotic and driven by the IKK cascade, while the second inflammatory response in senescence is IKK and proteasome independent, triggered by repression of IκBα mRNA synthesis. DNA damage induces a biphasic NF‐κB activation with functionally different response genes and activation mechanisms. The first, immediate phase is triggered by ATM/PARP1/TRAF6/IKK‐ and proteasome‐mediated IκBα proteolysis, and drives anti‐apoptotic genes. The second NF‐κB phase is activated days later during senescence and causes manifestation of the senescence‐associated secretory phenotype (SASP). A switch in RelA/p65 phosphorylation at Ser468 causes loss of NFKBIA/IκBα expression and IKK/proteasome‐independent NF‐κB activation in senescence. Abstract : DNA damage induces two kinetically and functionally distinct phases of NF‐κB activation, the first being anti‐apoptotic and the non‐canonical second wave inducing the senescence‐associated secretory phenotype (SASP).